2012
DOI: 10.1016/j.jns.2011.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Writing errors in ALS related to loss of neuronal integrity in the anterior cingulate gyrus

Abstract: showed that writing errors in our patients with ALS were related to dysfunction in the anterior cingulate gyrus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Defining the type and degree of language impairment in PD patients is hampered by a lack of generally recognized clinical criteria. The WAB [ 19 ] is an accepted method for assessing language abilities in many neurological diseases including stroke [ 26 , 27 ], amyotrophic lateral sclerosis [ 28 ], corticobasal degeneration syndrome [ 29 ], and brain tumor [ 30 ]. The WAB aphasia quotient (AQ) provides a global measure of aphasia severity [ 31 ] and was found appropriate for assessing non-fluent aphasia [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Defining the type and degree of language impairment in PD patients is hampered by a lack of generally recognized clinical criteria. The WAB [ 19 ] is an accepted method for assessing language abilities in many neurological diseases including stroke [ 26 , 27 ], amyotrophic lateral sclerosis [ 28 ], corticobasal degeneration syndrome [ 29 ], and brain tumor [ 30 ]. The WAB aphasia quotient (AQ) provides a global measure of aphasia severity [ 31 ] and was found appropriate for assessing non-fluent aphasia [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate whether loss of GABAergic inhibition contributes to cortical hyperexcitability in ALS, PET studies were conducted using the GABA A receptor ligand [ 11 C]-Flumazenil. These studies showed widespread reductions in binding in ALS patients compared to controls (52), and found that reduced binding in the frontal lobes (55) and anterior cingulate gyri (56) in ALS patients correlated with poorer performance on language tasks. Additionally, patients with slowly progressive ALS caused by SOD1 D90A mutations had smaller reductions in binding compared to sporadic ALS patients (53).…”
Section: The Development Of Pet Imaging In Alsmentioning
confidence: 99%
“…Moreover, the WEI was found to be mildly associated with disease duration. Yabe et al . (2012) again found that the WEI [Tsuji-Akimoto et al ., 2010] was able to discriminate ALS patients from HCs, additionally showing that it was related to bilateral right-greater-than-left anterior cingulate cortex (ACC) dysfunction as assessed by positron emission tomography (PET).…”
Section: Resultsmentioning
confidence: 99%
“…EF deficits as contributing to writing errors appears also to be supported as far as neural correlates are concerned – since frontal cortices often appeared to be involved in MND patients showing dysgraphic features [ e . g ., Yabe et al ., 2012].…”
Section: Discussionmentioning
confidence: 99%